USE OF DAPAGLIFLOZIN (FORXIGA) IN THE TREATMENT OF HEART FAILURE: CURRENT EVIDENCE AND CLINICAL EFFICACY - Crema, Júlia Chermont; da Silva, Alessandra Matsuoka Borges; Schonarth, Ana Paula; de Souza, Kelen Marques; Gonçalves, Fernanda Dominique de Souza; Gabriel, Felipe Veiga Kezam; Xavier, Suzielly Ramos Barbosa Lima; Santiago, Luigi Mestrinelli; Pereira, Gardênia Santos; Hatisuka, Felipe Romão; Ramos, Vitor de Castro; Sousa, Áureo Nios de Oliveira; et al. (Seven Editora, 2026)
Heart failure remains one of the leading causes of cardiovascular morbidity and mortality worldwide, being associated with high hospitalization rates, progressive functional impairment, and significant socioeconomic burden. In this context, dapagliflozin, a sodium-glucose cotransporter-2 (SGLT2) inhibitor, has emerged as an important therapeutic strategy in the contemporary management of heart failure, demonstrating cardiovascular and cardiorenal benefits that extend beyond glycemic control. This study aimed to analyze current scientific evidence regarding the clinical efficacy of dapagliflozin in the treatment of heart failure, emphasizing its effects on cardiovascular mortality, hospitalizations, quality of life, functional capacity, and renal protection. This is an integrative literature review with a qualitative and descriptive approach, conducted through searches in PubMed, SciELO, and ScienceDirect databases using descriptors related to dapagliflozin, heart failure, and cardiovascular outcomes. Studies published between 2019 and 2023 were included, comprising randomized clinical trials, systematic reviews, meta-analyses, and international guidelines. The main findings demonstrated significant reductions in heart failure hospitalizations, cardiovascular mortality, and episodes of clinical worsening, in addition to improvements in quality of life and preservation of renal function across different phenotypes of the disease. The DAPA-HF and DELIVER trials were particularly highlighted as milestones in consolidating SGLT2 inhibitors as a fundamental therapeutic component in heart failure management. It is concluded that dapagliflozin represents an important advancement in the treatment of heart failure, promoting consistent clinical benefits and contributing to a more integrated and multidimensional therapeutic approach aimed at optimizing cardiovascular and cardiorenal outcomes.